3 - Strengthening Peace Research and Peace Education in African Universities - Kenneth Omeje (African Sociological Review, 2015)
This paper explores the problems and challenges of promoting and embedding conflict-sensitive peace education in African higher education, especially in the universities. The paper also proffers some constructive policy recommendations and intervention strategies. Universities have traditionally been concerned with imparting specialized knowledge and skills in various fields of study capable of helping beneficiaries to make useful contributions to societal development and also earn meaningful livelihood from a legitimate occupation. There is increasing interest in the role of higher education in promoting peace and security at all levels of society, particularly in volatile conflict-prone and war-affected societies. This research has been mainly conceived to help strengthen the growing body of policy-relevant knowledge on the functional application of peace research and peace education in Africa.